2015
DOI: 10.1118/1.4932631
|View full text |Cite
|
Sign up to set email alerts
|

The development and verification of a highly accurate collision prediction model for automated noncoplanar plan delivery

Abstract: An individualized collision prediction model for the purpose of noncoplanar beam delivery was developed and verified. With the model, the study has demonstrated the feasibility of predicting deliverable beams for an individual patient and then guiding fully automated noncoplanar treatment delivery. This work motivates development of clinical workflows and quality assurance procedures to allow more extensive use and automation of noncoplanar beam geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 31 publications
1
78
0
1
Order By: Relevance
“…The delivery time of 4π plans involving a large number of beams can be excessively long in the manual mode. This limitation will be overcome using automating non-coplanar plan delivery [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery time of 4π plans involving a large number of beams can be excessively long in the manual mode. This limitation will be overcome using automating non-coplanar plan delivery [19]. …”
Section: Discussionmentioning
confidence: 99%
“…4π optimization begins with a candidate pool of 1162 non-coplanar beams, each 6° apart in the 4π solid angle space. Using a computer assisted design (CAD) model of the Varian TrueBeam machine and a 3D human surface model, each angle is simulated and subsequently eliminated if a collision is predicted between the gantry and the couch or patient [19]. The remaining beams were divided into 5 × 5 mm 2 beamlets, whose dose was calculated using convolution/superposition and Monte Carlo calculated 6MV polyenergetic kernels as described previously [20, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Collision of the machine with the patient during treatment, however, is still unsolved for these non‐isocentric, and non‐coplanar treatments. Most studies focus on collision prediction of the treatment plan, but not real‐time monitoring . Since the camera is on the couch, with the combination of the 3D computer‐aided design of the linac, it is feasible to build a real‐time collision avoidance system — if we know the location of patient relative to the machine, the collision can be avoided during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported that the quadrature sum of the translational uncertainties (maximum value was 1.09 mm at couch angle of 270° using a weight of 70 kg) mostly depended on couch angles rather than weights of the phantom. Noncoplanar beams (or arcs) are commonly used in SRS/SRT treatment with a linear accelerator to improve dose conformity and normal tissue sparing . Murphy et al analyzed the patterns of patient movements during frameless image‐guided radiosurgery with the CyberKnife.…”
Section: Introductionmentioning
confidence: 99%